The mean end chain theory for private label brand (PLB) / Azahar Yusoff, Hatinah Abu Bakar and Alinawati Ab Aziz - Yusoff, Azahar; Abu Bakar, Hatinah; Ab Aziz, Alinawati (2022)
For Malaysians, save money and health benefits are identified as views that motivate consumers purchase of private label brand (PLB). The purpose of this paper is to investigate how consumers from a developing country background such as in Malaysia decide to purchase a Private Label Brand (PLB) product. Although this paper is a conceptual paper in order to investigate the scenario of PLB consumer acceptance in Malaysia but the literature discussed in this paper is using the Scopus database and high citation (restricted from 2011 to 2021) which help in generalizing the study. The use of the means-end chain (MEC) approach is discussed as a measure of attributes, consequences and values of locally produced products. It is better to comprehend the MEC element in consumer decision making so that it can be used as guidance in PLB. The usefulness of MEC studies in the framework of a consumer-oriented food product design is evaluated and future research trends in this area are discussed and this study identifies the consumers' motivations in buying local foods and examines the motivation differences between rural and urban locations. The findings are hoped can give insights for the government and individual businesses.